2022
DOI: 10.1186/s12885-022-10034-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model of axillary lymph node status using automated breast ultrasound (ABUS) and ki-67 status in early-stage breast cancer

Abstract: Background Automated breast ultrasound (ABUS) is a useful choice in breast disease diagnosis. The axillary lymph node (ALN) status is crucial for predicting the clinical classification and deciding on the treatment of early-stage breast cancer (EBC) and could be the primary indicator of locoregional recurrence. We aimed to establish a prediction model using ABUS features of primary breast cancer to predict ALN status. Methods A total of 469 lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…Age, tumor location, histological grade and Ki-67 have also been found to be independent risk factors for ALNM in earlier research. Nevertheless, due to variances in sample size and population selection, these parameters did not show significant differences in the logistic regression analysis of the present study ( 37 , 38 , 50 – 52 ).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Age, tumor location, histological grade and Ki-67 have also been found to be independent risk factors for ALNM in earlier research. Nevertheless, due to variances in sample size and population selection, these parameters did not show significant differences in the logistic regression analysis of the present study ( 37 , 38 , 50 – 52 ).…”
Section: Discussioncontrasting
confidence: 52%
“…A number of studies have established a close association between clinicopathological features of tumors and ALNM (36)(37)(38). In the present study, a nomogram model was developed to predict the risk of ALNM in patients with EBC and cN0.…”
Section: Discussionmentioning
confidence: 97%
“…These studies indicated good diagnostic performance of ABUS. Recently, several studies [ 12 , 32 ] showed some ABUS imaging features were significantly correlated with ALN status. In our study, ABUS model displayed adequate discriminative ability (AUC 0.772 in the training set and 0.736 in the test set).…”
Section: Discussionmentioning
confidence: 99%
“…As an emerging three-dimensional imaging technique, Automated Breast Ultrasound (ABUS), addresses the limitations of conventional handheld ultrasound (HHUS) and automatically scans the breast based on special high-frequency broadband sensors [ 10 ]. Several recent studies [ 11 , 12 ] have shown that some unique features of ABUS, although they are also visual assessment and qualitative descriptions, may provide additional information for breast lesions. Specifically, retraction phenomenon appears as a satellite model around the lesion, with high sensitivity (80%–89%) and specificity (96%–100%) for breast cancer [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nomogram is recognized as a good predictive tool with good discriminating power and has been widely used to predict the type and prognosis of different diseases (Iasonos et al, 2008;Balachandran et al, 2015). The combined model (training set AUC = 0.869, validation set AUC = 0.820) was better than the ultrasound-based model (training set AUC = 0.844, validation set AUC = 0.771) in predicting axillary lymph node metastasis, and was also better than some other clinical prediction models (Gao et al, 2022;Geng et al, 2022;Wang et al, 2022), which may be related to the inclusion of ultrasonic features of lymph nodes in this study. The combined nomogram had an excellent ability to predict axillary lymph node metastasis, which can help clinicians predict axillary lymph node metastasis before surgery.…”
Section: Discussionmentioning
confidence: 95%